A Medieval Perspective on the Control of Charisma: Henricus Herp’s (d. 1477) Analysis of Grace and Visions in The Mirror of Perfection - Knibbe, David (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This article explores the tension between charismatic and institutionalized religion in the late medieval context, from the perspective of Henricus Herp’s (†1477) The Mirror of Perfection. Classical sociological theories cast charismatic authority as structurally opposed to institutional religion. Herp’s perspective on the social functioning of charisma complicates this perspective. This study situates Herp’s views within the historical context of the fifteenth century Observant Reform and the broader mystical tradition, particularly that of Jan van Ruusbroec. Herp recognizes the dangers of visions and divine gifts for the mystic and society. Rather than advocating institutional control, he locates the necessary discernment within the individual’s ascetic orientation. In this way, Herp reconfigures the tension between charisma and institution: not by suppressing the former, but by interiorizing its regulation and control. The disruptive potential of divine gifts should, in Herp’s view, be ultimately contained not by an institution but by the individual.